OZONIOTHERAPY IN THE TREATMENT OF PERIORBITAL CUTANEOUS HYPERCHROMIA: CLINICAL CASE REPORT - Lima Rodrigues Silva, Tassia; Rech Feldmann, Cristina (Health and Society, 2022)
Periorbital cutaneous hyperchromia, popularly called “olheira”, corresponds to one of the main complaints of patients looking for aesthetic treatments. One of the most famous phrases written by Leonardo da Vinci describes the eyes as being the window to the soul, for this fact, orbital hyperpigmentation directly interferes with the patient’s self-esteem, and can impact their quality of life, by producing the appearance of tiredness and fatigue. aging. Periorbital cutaneous hyperchromia is characterized by darkening of the eye area, its etiology is complex and multifactorial, being caused by several exogenous and endogenous factors. There are numerous treatments described in the literature that improve this change, ozone therapy is one of them for combating swelling, circles and bags under the eyes. The objective of this work was to review the literature related to the use of ozone therapy for the treatment of periorbital skin hyperchromia and, through a clinical report, to demonstrate the result obtained through a protocol of weekly application of medicinal ozone in the periorbital region. The monitoring of the results of the applications was carried out through photographic records, showing a significant improvement in hyperchromia at the end of the eighth session.